2016
DOI: 10.1136/bmj.i5130
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter versus surgical aortic valve replacement in patients with severe aortic stenosis at low and intermediate risk: systematic review and meta-analysis

Abstract: Objective To examine the effect of transcatheter aortic valve implantation (TAVI) versus surgical replacement of an aortic valve (SAVR) in patients with severe aortic stenosis at low and intermediate risk of perioperative death.Design Systematic review and meta-analysisData sources Medline, Embase, and Cochrane CENTRAL.Study selection Randomized trials of TAVI compared with SAVR in patients with a mean perioperative risk of death <8%.Review methods Two reviewers independently extracted data and assessed risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 37 publications
2
82
0
3
Order By: Relevance
“…[3][4][5] With the expanding indication and prolongation of life expectancy after TAVI, it is speculated that risk stratification and long-term management of HF may be the next challenge facing physicians. [3][4][5][6] For example, a recent meta-analysis that predominantly included intermediate-risk patients with AS demonstrated that transfemoral TAVI is associated with more severe HF symptoms than SAVR during 2-year follow-up. 6 N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a hormone released by the cardiac ventricles as a result of elevated end-diastolic pressure overload.…”
Section: Open Accessmentioning
confidence: 99%
“…[3][4][5] With the expanding indication and prolongation of life expectancy after TAVI, it is speculated that risk stratification and long-term management of HF may be the next challenge facing physicians. [3][4][5][6] For example, a recent meta-analysis that predominantly included intermediate-risk patients with AS demonstrated that transfemoral TAVI is associated with more severe HF symptoms than SAVR during 2-year follow-up. 6 N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a hormone released by the cardiac ventricles as a result of elevated end-diastolic pressure overload.…”
Section: Open Accessmentioning
confidence: 99%
“…Two systematic reviews and meta-analyses (one for efficacy9 and one for prognosis10) provided the evidence for a guideline panel to make recommendations for use of transcatheter aortic valve implantation (TAVI) and surgical aortic valve replacement (SAVR) 11. The meta-analysis assessing the efficacy of these two therapies showed that TAVI, originally designed for patients at high risk for SAVR, can be extended to low-surgical to moderate-surgical risk patients 10.…”
Section: Examples Of Recent Meta-analysis Impacting Guideline Recommementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Compared with SAVR, transfemoral TAVI reduced mortality and stroke, life threatening bleeds, atrial fibrillation, and acute kidney injury at two years, but increased heart failure, major vascular complications, pacemaker insertion, and need for aortic valve reintervention within 2 years (see infographic). 10 In contrast, transapical TAVI may increase mortality and stroke compared with the surgical approach. The results for mortality, stroke, and acute kidney injury were based on a subgroup analysis for transfemoral versus transapical approach, deemed credible by the review authors according to specific criteria.…”
Section: The Evidencementioning
confidence: 99%